(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Millions of people all around the world were negatively impacted by the unusualsocioeconomic predicament brought on by the COVID-19 pandemic of 2020. On March 24, 2020, Indiadeclared a lockdown as a preventative measure to avoid the spread of the pandemic, which resulted inthe loss of employment for migrant workers whose livelihood depended on daily wages. Many of theseworkers were women who were engaged in domestic work and relied solely on the income from theiremployment in order to make ends meet. This study sheds light on the situation of women who, becauseof the pandemic’s economic effects, experienced significant psychological and social challenges.25 migrant female household labors were sampled from Delhi city during the lockdown phase of thepandemic, and the study used a sequential explanatory design. The findings of the study shed light onthe negative effects of economic hardship on the mental health and quality of life of the group underconsideration. By demonstrating that state measures are insufficient to guarantee even the most basicneeds of migrant female household labors, a critical analysis of the policies and programmes highlightsthe need for social action in the form of lobbying for more humanitarian laws that ensure social securityfor the underprivileged.